Sunscreens containing zinc oxide nanoparticles can trigger oxidative stress and toxicity to the marine copepod Tigriopus japonicus. (May 2020) - Wong, Stella W.Y.; Zhou, Guang-Jie; Leung, Priscilla T.Y.; Han, Jeonghoon; Lee, Jae-Seong; Kwok, Kevin W.H.; Leung, Kenneth M.Y.
Abstract: The study, for the first time, evaluated the leaching rate of zinc oxide nanoparticles (nZnO) from human skins which were applied with three commercial sunscreens containing nZnO as an active ingredient. The leaching rate of nZnO varied greatly among the sunscreens, with a range of 8–72% (mean ± SD: 45% ± 33%). We further investigated their toxicities to the marine copepod Tigriopus japonicus . We found that 96-h median lethal concentrations of the three sunscreens to T. japonicus were > 5000, 230.6, and 43.0 mg chemical L −1, respectively, equivalent to Zn 2+ concentrations at >82.5, 3.2, and 1.2 mg Zn L −1, respectively. Exposure to the individual sunscreens at environmentally realistic concentrations for 96 h led to up-regulation of antioxidant genes in T. japonicus, while they triggered the release of reactive oxygen species based on the results of in vivo assays. Evidently, these nZnO-included sunscreens can cause oxidative stress and hence pose risk to marine organisms. Highlights: Leaching rates of nZnO from the sunscreens applied on human skin ranged from 8 to 72%. At elevated levels, nZnO-included sunscreens were toxic to the copepod T. japonicus . Their toxicities were associated with releases of nZnO and Zn 2+ from the sunscreens. Exposure to the sunscreens altered the expression of antioxidant genes in copepods. Such exposures triggered the release of in vivo ROS and caused oxidative stress.